Discovery of Novel Allosteric Non‐Bisphosphonate Inhibitors of Farnesyl Pyrophosphate Synthase by Integrated Lead Finding. Issue 11 (18th September 2015) - Marzinzik, Andreas L.; Amstutz, René; Bold, Guido; Bourgier, Emmanuelle; Cotesta, Simona; Glickman, J. Fraser; Götte, Marjo; Henry, Christelle; Lehmann, Sylvie; Hartwieg, J. Constanze D.; Ofner, Silvio; Pellé, Xavier; et al.
Abstract: Farnesyl pyrophosphate synthase (FPPS) is an established target for the treatment of bone diseases, but also shows promise as an anticancer and anti‐infective drug target. Currently available anti‐FPPS drugs are active‐site‐directed bisphosphonate inhibitors, the peculiar pharmacological profile of which is inadequate for therapeutic indications beyond bone diseases. The recent discovery of an allosteric binding site has paved the way toward the development of novel non‐bisphosphonate FPPS inhibitors with broader therapeutic potential, notably as immunomodulators in oncology. Herein we report the discovery, by an integrated lead finding approach, of two new chemical classes of allosteric FPPS inhibitors that belong to the salicylic acid and quinoline chemotypes. We present their synthesis, biochemical and cellular activities, structure–activity relationships, and provide X‐ray structures of several representative FPPS complexes. These novel allosteric FPPS inhibitors are devoid of any affinity for bone mineral and could serve as leads to evaluate their potential in none‐bone diseases. Abstract : Beyond the bone : Farnesyl pyrophosphate synthase (FPPS) is an important target for osteoporosis and bone metastases, and holds promise for a number of non‐bone diseases, including cancer, parasitic infections, progeria, and Alzheimer's disease. Herein we describe two novel chemotypes of allosteric FPPS inhibitors. These are useful leads to evaluate the therapeutic potential of FPPS inhibitors for these new indications.